Literary Sociology as a Theoretical Approach to Literary Study in the Novel "Salah Asuhan" by Abdoel Moeis - Rahmawati Rahmawati (Research in Education, Technology, and Multiculture, 2023)
Abstract: Literature is a work that writers use to express various forms of feelings. Literary works are the result of the abilities possessed by writers in terms of imagination and imagination, but literary works cannot be separated from certain political ideologies. This research uses a qualitative descriptive method with a literature review. The data collection techniques used were data reduction, data presentation, and drawing conclusions which focused on the political point of view in the novel "Salah Asuhan" by Abdoel Moeis. The event of hegemony occurs in the novel because the character in the role changes citizenship to follow Western culture because of his fascination and wants to escape from the constraints of Eastern cultural rules.   Keywords: hegemony, politics, literary works